2017
DOI: 10.1002/arch.21373
|View full text |Cite
|
Sign up to set email alerts
|

The dipteran parasitoid Exorista bombycis induces pro‐ and anti‐oxidative reactions in the silkworm Bombyx mori: Enzymatic and genetic analysis

Abstract: Hymenopteran parasitoids inject various factors including polydnaviruses along with their eggs into their host insects that suppress host immunity reactions to the eggs and larvae. Less is known about the mechanisms evolved in dipteran parasitoids that suppress host immunity. Here we report that the dipteran, Exorista bombycis, parasitization leads to pro-oxidative reactions and activation of anti-oxidative enzymes in the silkworm Bombyx mori larva. We recorded increased activity of oxidase, superoxide dismuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One cellular immune reaction against invading parasitoid eggs and larvae is encapsulation with hemocytes followed by melanization ( Yamashita et al, 2019 ; Yang et al, 2021 ). Recent studies identified enhanced expression of innate immunity components of toll and melanization pathways, cytokines or proteolytic enzymes, and oxidative reactions in B. mori following Exorista sorbillans parasitoidism ( Pradeep et al, 2013 ; Anitha et al, 2014 ; Jayaram et al, 2014 ; Makwana et al, 2017 ; Pooja et al, 2017 ; Xu et al, 2019 ). We showed here that around 35% parasitized larvae have undergone successful larval–pupal transition and around 25% of the successful pupated parasitized hosts could eliminate tachinid larvae either in larval or pupal stage and undergo successful eclosion.…”
Section: Discussionmentioning
confidence: 99%
“…One cellular immune reaction against invading parasitoid eggs and larvae is encapsulation with hemocytes followed by melanization ( Yamashita et al, 2019 ; Yang et al, 2021 ). Recent studies identified enhanced expression of innate immunity components of toll and melanization pathways, cytokines or proteolytic enzymes, and oxidative reactions in B. mori following Exorista sorbillans parasitoidism ( Pradeep et al, 2013 ; Anitha et al, 2014 ; Jayaram et al, 2014 ; Makwana et al, 2017 ; Pooja et al, 2017 ; Xu et al, 2019 ). We showed here that around 35% parasitized larvae have undergone successful larval–pupal transition and around 25% of the successful pupated parasitized hosts could eliminate tachinid larvae either in larval or pupal stage and undergo successful eclosion.…”
Section: Discussionmentioning
confidence: 99%
“…A 25 μl reaction mixture contained 2.5 μl cDNA template, 1 pmol each of the forward and reverse primers, and 12.5 μl SYBR Green qPCR master mix (1×) containing 5 mM MgCl 2. The thermal program used was given as early (Makwana et al, 2017). Gene encoding ribosomal protein S5 from B. mori (NM_001043794) was used as a housekeeping gene that showed consistent expression in different tissues (Butte et al, 2001) and hemocyte samples used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A 25 μl reaction mixture contained 2.5 μl cDNA template, 1 pmol each of the forward and reverse primers, and 12.5 μl SYBR Green qPCR master mix (1×) containing 5 mM MgCl 2. The thermal program used was given as early (Makwana et al, 2017).…”
Section: Total Rna Extraction From E Bombycis Larval Tissue Cdna Synt...mentioning
confidence: 99%
See 1 more Smart Citation
“…mori [10]. In the early stage of parasitization, the antioxidative enzyme levels are maintained at a high level in silkworm hemocytes, revealing the continuous need for antioxidative enzymes to prevent immune suppression by enduring parasitism in the host [11]. Under parasitic influence, the expressions of cell apoptosis-associated genes, including autophagy 5-like ( Atg5 ), apoptosis-inducing factor ( AIF ), and nedd2-like caspase, are enhanced in the larval integument of B .…”
Section: Introductionmentioning
confidence: 99%